3
Аноним
Математика
07 декабря 11:48

Упростите выражение (2m^5n^4)^7×(4m^3n^5)^2 :(2m^4n^4)^10

Ответ или решение1

Беспалова Надежда

(2 * m^5 * n^4)^7 * (4 * m^3 * n^5)^2 : (2 * m^4 * n^4)^10 = (2^7 * m^(5 * 7) * n^(4 * 7) * 4^2 * m^(3 * 2) * n^(5 * 2)) : (2^10 * m^(4 * 10) * n^(4 * 10)) = (2^7 * m^35 * n^28 * 4^2 * m^6 * n^10) : (2^10 * m^40 * n^40) = (2^(7 + 4) * m^(35 + 6) * n^(28 + 10)) : (2^10 * m^40 * n^40) = 2^(11 - 10) * m^(41 - 40) * n^(38 - 40) = 2 * m * n^(-2) = 2 * m/n^2;

Ответ: 2 * m/n^2.

0 / 10000
ВходРегистрация

Вход

или

Регистрация